Strength training for Chinese swimmers and its effect upon androgenic responses and psychological scores - Chen, N.; Lin, J.; Yu, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Strength training (STT) is one mode of training adopted by the Chinese swimming team. Under the condition of STT, there may be interrelationship between the androgenic responses and some psychological abilities. The aim of this study was to investigate the relative change in total testosterone (TT) levels and some psychological abilities in young swimmers after STT. Methods Before and after 10 weeks STT, resting serum TT in 11 male swimmers whose mean age was 17 years, were measured using a radioimmunoassay method, then the testing of two kinds of sports psychological index took place before and after STT. Sports cognitive abilities, including synthetic reaction (SR), motion sense time estimation ability (MST), spatial direction judgment ability (SDJ), time & spatial judgment ability (STJ), visual memory ability (VM) and operation thinking ability (OT), and (2) mental energy test, included achievement motive test (AMT), self-confidence test (SCT). Results After 10 weeks training, mean serum TT decreased significantly (14.92%, from 446.11 124.62ng/dl to 389.05 128.47ng/dl, P<0.05). The psychological abilities also had a change. The sports cognitive abilities increased significantly. Especially OT, VM and STJ increased obviously (39.27%, 33.41%, 40.82%, P<0.01). The other four kinds of sports cognitive abilities (SRT, SR, MST, SDJ) had also enhanced evidently (P<0.05 ) after STT. Mental energy testing effect simultaneously reflected well. Achievement motive level of young swimmers increased clearly after STT compared with baseline (mean score from 23.47 8.75 to 33.06 7.22, raised 40.92% ,P<0.01). On the other hand, SCT indicated self-encouragement level of participants also improved. Although physical function has decreased and fatigue had appeared in STT, most players felt vigorous and spirited. A non-linear and complex relationship between serum TT and mean score of psychological testing ( r =0.637,P<0.01) was observed. Discussion / Conclusions According to general opinion, the sport psychological functions should decrease while the body is fatigued from high intensity training. It was said that male hormone responses could activate potential psychological energy. A certain level of male hormone is important for physical foundation to keep good cognitive psychological abilities and mental energy. It is important to be aware of the athlete`s interrelated relationship of physiology and psychology for long term and intensity training. However, the current findings indicate participants cognitive abilities and mental energy increased on the contrary. The testing results show that sports cognitive psychological abilities and mental energy increased while androgenic responses decreased. A possible cause was the training effect of STT. The training mode of STT is a repetition of training style with simulation of competition in training process. The competition situation in training process of STT could activate the psychological energy of athletes, achievement motive and self-confidence, and enhance sports cognitive abilities of athletes, including synthetic reaction, motion sense time estimation ability, spatial direction judgment ability, time & spatial judgment ability, visual memory ability and operation thinking ability. Although the androgenic responses decreased, it was remedied by psychological abilities and mental energy increasing the sports ability and energy levels. It showed that the vigor and spirit could compensate for the decreas in physical function. Perhaps there is some regulating or controlling mechanism and mutual relationship between physical function and psychological ability or mental energy in the competition situation stimulation of training.